Clinical observations of patients with metastatic castration-resistant prostate cancer living in the Tambov region - P. G. Berezin; V. V. Milovanov; A. A. Ivannikov; V. A. Kuleshkov; K. M. Nyushko (Исследования и практика в медицине)
Treatment of patients with metastatic castration-resistant prostate cancer in clinical practice is a vital necessity and a challenging task since the causes of castration resistance are not fully understood. Adherence to treatment regimens in accordance with the National Clinical Guidelines allows to achieve an increase in both overall survival and progression-free survival, as well as to reduce the mortality rate in this category of patients. Administration of 1st-line treatment regimens stabilizes the disease in the majority of pancreatic cancer patients; in some cases, the disease becomes aggressive, distant metastases appear, most oﬅen in bones, lymph nodes, and internal organs, as demonstrated by three clinical observations presented in this article. The administration of enzalutamide (in 2 cases) and abiraterone acetate (in 1 case) at the stage of resistance to castration therapy allowed to obtain a complete “response” from visceral lesions, stabilise bone metastatic foci and increase the life expectancy of patients.